Analisis Isu Gempa Megathrust 2024 Melalui Akun Youtube Badan Nasional Penanggulangan Bencana Indonesia - Budi Assaudi; Wahyutama (Comit: Communication, Information and Technology Journal, 2025)
The news release issued by BMKG regarding the 2024 megathrust earthquake has been widely spread in mainstream media and social media. The news only shows the phenomenon of the megathrust earthquake, the narrative has become a polemic in the community. The results of the research found in the BNPB Indonesia Youtube account video with the topic of Preparedness Tips Facing Megathrust Potential using Teun Van Dijk's discourse analysis in the text dimension found microstructure elements that reveal the main problems, namely the megathrust issue and the megathrust information gap in society. Meanwhile, social cognition analysis produces the most dominant scheme, namely the event scheme. In social cognition, there are two discourses that are emphasized, namely that there are still many people on the coast who do not know the threat of megathrust earthquakes and the events of earthquakes and tsunamis that have occurred that have claimed hundreds of lives. The implication of the social context dimension found that the communicator directed the discourse from the megathrust issue to the tsunami phenomenon and identified the characteristics of the tsunami caused by the earthquake contained in the language and discourse in the video.